A Novel Intervention Platform for Service Members With Subjective Cognitive Complaints: Implementation, Patient Participation, and Satisfaction. - Sullivan, Katherine W; Law, Wendy A; Loyola, Laura; Knoll, Martin A; Shub, Daniel E; French, Louis M (Military Medicine)
Introduction: Program overview of a novel cognitive training platform at Walter Reed National Military Medical Center (WRNMMC) for service members with subjective cognitive complaints: analysis of patient participation, satisfaction with the program, and perceived areas of improvement.Materials and Method: Retrospective review of 1,030 participants from November 2008 through May 2017. Data were obtained within an approved protocol (WRNMMC-EDO-2017-0004/# 876230).Results: The program has shown growth in numbers of referrals, types of patient populations served, and patient visits. Patients report satisfaction with the program and endorse improvements in cognitive functions.Conclusions: This program model may benefit other military facilities looking to provide and assess novel therapeutic approaches.